COMPLICATIONS OF ORTHODONTIC TREATMENT OF DENTOALVEOLAR ANOMALIES IN CHILDREN - A.V. Pachevska; Yu.V. Filimonov (Український стоматологічний альманах)
In the world 60-90% of children suffer from caries, gingivitis, periodontal diseases, millions of children start orthodontic treatment every year. In Ukraine regular dental epidemiological study of local researchers to assess the effeciency of national programs of primary prevention of dental diseases is hold. One of the priority areas of research is the study of dental diseases in Ukraine children. According to scientists of our country it is causing the increasing concern teeth and jaws dental abnormalities among children and adolescents, and the secondary complications that arise during orthodontic treatment. In addition, the increasing attention is paid to the most modern and effective methods of early diagnosis and removal. Among 43% of Ukrainian children with common dental pathology periodontal diseases occur in 30%. In their research scientists note periodontal disease in 70% of children is combined with dentoalveolar anomalies. Today it is established that endogenous and exogenous factors are important for orthodontic treatment: environmental conditions, oral hygiene, microbiocenosis state of the oral cavity, biochemical composition of oral fluid, action of orthodontic appliances, heredity. By this explains that on the one hand maxillofacial anomalies and poor oral hygiene are the most risk factors for the occurrence of periodontal diseases and the other diseases. It is indisputable that periodontal diseases lead to strain and complicate of orthodontic treatment. In addition, the apparatus treatment is an additional stress on periodontal tissue, orthodontic appliances complicate hygiene procedures. One of the important factors in the etiology of dental diseases during orthodontic treatment of teeth anomalies in children is the changing of the composition of oral microflora, dysbiosis. Dysbiosis has a negative effect on the state of the oral cavity. Conducted by the authors of microbiological analysis in patients with periodontal disease was showed that a significant number of patients have the drug resistance for major periodontal pathogens to conventional antibiotic therapy. This explains the significant additional complexity in the implementation of a full comprehensive prevention and treatment of complications during orthodontic treatment teeth anomalies.